1998
DOI: 10.1046/j.1365-2567.1998.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific antigen targeting to surface IgE and IgG on mouse bone marrow‐derived mast cells enhances efficiency of antigen presentation

Abstract: SUMMARYThe discovery that bone marrow-derived mast cells can express major histocompatibility complex class II molecules and act as antigen-presenting cells prompted us to evaluate this function when antigen is internalized through fluid-phase endocytosis or via specific uptake by using IgG and IgE antibodies. This study was performed using a specific T-cell hybridoma developed against Lol p 1, the major allergen of grass pollen Lolium perenne. Expression of FccR and FceRI by mast cells led us to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…The capacity of MCs to harbor allergens may even contribute to the high levels of allergen-specific IgE Abs (atopy) observed in the circulation of individuals suffering from allergy. It has been reported that MCs in the skin during contact hypersensitivity reactions trafficked to the regional lymph nodes where Ag-specific immunity is developed (33,38). Conceivably, MCs that phagocytosed allergens in peripheral body sites also traffic to regional lymph nodes and directly release allergens to APCs in the nodes, thereby facilitating the development of allergen-specific immune responses, including the generation of allergen-specific IgE Abs.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of MCs to harbor allergens may even contribute to the high levels of allergen-specific IgE Abs (atopy) observed in the circulation of individuals suffering from allergy. It has been reported that MCs in the skin during contact hypersensitivity reactions trafficked to the regional lymph nodes where Ag-specific immunity is developed (33,38). Conceivably, MCs that phagocytosed allergens in peripheral body sites also traffic to regional lymph nodes and directly release allergens to APCs in the nodes, thereby facilitating the development of allergen-specific immune responses, including the generation of allergen-specific IgE Abs.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, only IgG receptors IIb2 and III are involved in phagocytosis of antigen‐coated erythrocytes (reviewed in 5). Very recently, it was also shown that murine MC uptake of IgE complexed to a pollen allergen (Lol p1) was enhanced compared to similarly complexed IgG (13).…”
Section: Phagocytosis and Antigen Uptakementioning
confidence: 99%
“…Apart from the data on innate immunity, the well‐documented activity in the elimination of parasitic infestations (94) and their potential role in atopy on the basis of effects on allergen presentation and IgE synthesis (13, 66, 72, 73), evidence for the immune function of MC in other pathological conditions is weak or fragmentary (Table 4).…”
Section: Immune Function In Specific Diseasesmentioning
confidence: 99%
“…This receptor is easily internalized and can deliver the allergen bound to IgE into a cathepsin-S-dependent pathway of MHC class II presentation [35]. In a slightly artificial model, Tkaczyk et al [36] showed in 1998 that FcεRI expressed on cultured murine mast cells may also facilitate the presentation of allergens to allergen-specific T cells. Importantly, the expression of the αγ2 FcεRI is unique for human APC and has not been demonstrated to be present on APC in rodents, and may account for the fact that mouse models for inhalation allergy require high allergen doses.…”
Section: Fcεrimentioning
confidence: 99%